Love in Latif Halmat's poetic texts: A Sociology View - Aso Omer Mustafa; Adnan Ahmed Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Our research, entitled "Love in The Poetic Texts of Latif Halmat", is an attempt to explain Latif Halmat's sociology view of love and reflection of that concept in his poetic texts. Also, finding the fundamental relationship between oneself and subject, as love and subjects as society and sociology. Because it is a single member of society, it becomes a source of literary text production. From here the relationship between literature and sociology appears as science. Our research consists of two parts: the first part (the concept of love) talks about the concept of love of personal and social dimensions and explains writers' views on this concept. Part Two: (Love by Latif Halmat) practices the concept of love as a social dimension in the poetic texts of Latif Halmat. The result was finally presented with several points.